Modern languages and Modern Learners: different scores among Asian immigrant minorities for academic and language skills development. - Figueiredo, Sandra (2018)
A total of 108 children belonging to six groups – Western Europe, Eastern Europe, Portuguese-speaking African countries, Latin America, Asia and China - were compared regarding tasks on verbal reasoning and vocabulary skill to examine nationality group effects on task performance and language proficiency. This study aims to verify whether students from different nationalities and learners of Portuguese as L2 evidence similar difficulty levels in tests on language skills. Results of MANOVA showed that nationality groups differed in a significant manner, in particular, two groups – from South Asia (Meridional) and from Latin America - whose performance was different for both tests. The Asian group evidenced more difficulty in vocabulary decoding and verbal reasoning when compared to other nationality groups. Higher scores were attained by the Latin American group whose language of testing had common features with the home language and therefore showed more overlapping. The influence of the covariable "Languages spoken at home" on the results was also confirmed, which suggests that nationality is a less strong predictor compared to the number of languages spoken at home. Results will be discussed from the point of view of individualized assessment and intervention according to immigrant school groups in European contexts.